2016
DOI: 10.1177/1555412015581710
|View full text |Cite
|
Sign up to set email alerts
|

Players’ Value Structure in Digital Games

Abstract: The rapid advancement of digital games has not only brought entertainment to consumers but also triggered gamers’ motivation to play. This study attempts to examine the structure of “attribute–consequence–value” chains of digital games based on the theoretical framework of means-end chains (MECs) and soft laddering interview technique. Results of the study reveal that players pay attention to game attributes including connection system, popular, graphic design, and diverse game genres. From these attributes, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
0
20
1
Order By: Relevance
“…For example, Sheng and Teo (2012) measured hedonic value through entertainment and aesthetics, while Ha, Yoon, and Choi (2007) proposed perceived pleasure and perceived attractiveness (PA) as factors that provide enjoyment and fun in MGs. Lin, Lin, and Yang (2017) suggested that game attributes, such as graphic design, contribute to the player's expectation of fun.…”
Section: Hedonic Value and Loyalty Intentionmentioning
confidence: 99%
“…For example, Sheng and Teo (2012) measured hedonic value through entertainment and aesthetics, while Ha, Yoon, and Choi (2007) proposed perceived pleasure and perceived attractiveness (PA) as factors that provide enjoyment and fun in MGs. Lin, Lin, and Yang (2017) suggested that game attributes, such as graphic design, contribute to the player's expectation of fun.…”
Section: Hedonic Value and Loyalty Intentionmentioning
confidence: 99%
“…Video games provide an important context for the understanding the construction of an identity in a virtual space (Kozinets and Kedzior 2009). Unlike the 'corporeal world' in which one's identity is largely constructed by social, economic, political, and other external cultural factors, a gamer's virtual identity is constructed by his/her choices, which leads to a sense of 'self' created in the virtual world (Hinsch and Bloch 2009) representing either an 'idealized' (Vicdan and Ulusoy 2008) or 'possible' self (Belk 2013), which is not necessarily possible in actual reality (Lin, Lin and Yang 2017;Molesworth and Denegri-Knott 2007b;Molesworth 2009). For instance, in this special issue, Baldwin (2018) sheds light on the conflict experienced by transgender people in actual reality and the ability they have to construct an idealized self in virtual reality.…”
Section: Market Society and Video Gamesmentioning
confidence: 99%
“…In order to construct an integrated developmental model and to guide our understanding in a qualitative thematic analysis, we selected 7 related theoretical models: (1) cognitive-behavioral model of pathological internet use [ 10 ], (2) a new model of media attendance [ 29 ], (3) model of compensatory internet use [ 30 ], (4) basic model of problematic internet use in youth [ 31 ], (5) differential-susceptibility to the media effects model [ 32 ], (6) reinforcing spirals model [ 33 ], and (7) player’s value structure in digital games [ 34 ]. In this section, we compare these 7 models and discuss the insights gained in relation to problematic internet use behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in the domain of game studies and consumer research, Lin et al [ 34 ] proposed the structure of attribute-consequence-value chains of digital game players. Using soft-laddering interviews and a theoretical framework of means-end chains, they revealed game attributes that players direct their attention to, including attributes such as the connection system, popularity, graphic design, and diverse game genres.…”
Section: Introductionmentioning
confidence: 99%